Hiroshima - Wandlungen der inneren Struktur und Region - Morikawa, Hiroshi; Kitagawa, Kenji (ERDKUNDE, 1963)
Since the second part of the 19th century many towns have grown with the social and economical modernization in Japan. With the growth of towns there have occurred the regional difference of their inner structure and the expansion of their tributary areas. We studied these changing patterns in Hiroshima City, which is situated in western Japan facing Seto-Inland Sea. The results of this investigation are as follows: 1. The origin of Hiroshima City is a typical castle town built in 1959. From 1870’ till the end of World War II it grew as a military town and the district centre in Chugoku districts. The inner structure in those days retained in many places that of the times of the castle town, in which the specialization of CBD function was not remarkable. After the terrible war disaster several bazaars were born in the terminal points in the peripheric of the burned areas. When the CBD was reconstructed, they have become sub-centres of business. The separation of the urban area by the delta-arms may have promoted the formation of such sub-centres. 2. Most of the present Hiroshima Prefecture belonged to the lord of Hiroshima in the feudal age. But its economical tributary area was, we think, not so large. In the coastal area there were large towns as close with each other in 1870’ as in these days, because Seto Inland Sea was the main route between Osaka and northern Kyushu. The market towns in the inland area, most of which were central places of lower order, lay scattered. With the urban growth of Hiroshima the hierarchization of central places become clear till the present day; near Hiroshima City we can recognize the system of central places as fig. 9. Since 1870’ few new central places have appeared in the coastal area in spite of the decline of many central places of lower order, while several new central places of lower order in the inland area have come into the world along new important traffic routes.